Alterations in plasma L-arginine and methylarginines in heart failure and after heart transplantation. (4th July 2018) - Lundgren, Jakob; Sandqvist, Anna; Hedeland, Mikael; Bondesson, Ulf; Wikström, Gerhard; Rådegran, Göran
Abstract: Objective . Endothelial function, including the nitric oxide (NO)-pathway, has previously been extensively investigated in heart failure (HF). In contrast, studies are lacking on the NO pathway after heart transplantation (HT). We therefore investigated substances in the NO pathway prior to and after HT in relation to hemodynamic parameters. Design. 12 patients (median age 50.0 yrs, 2 females), heart transplanted between June 2012 and February 2014, evaluated at our hemodynamic lab, at rest, prior to HT, as well as four weeks and six months after HT were included. All patients had normal left ventricular function post-operatively and none had post-operative pulmonary hypertension or acute cellular rejection requiring therapy at the evaluations. Plasma concentrations of ADMA, SDMA, L-Arginine, L-Ornithine and L-Citrulline were analyzed at each evaluation. Results. In comparison to controls, the plasma L-Arginine concentration was low and ADMA high in HF patients, resulting in low L-Arginine/ADMA-ratio pre-HT. Already four weeks after HT L-Arginine was normalized whereas ADMA remained high. Consequently the L-Arginine/ADMA-ratio improved, but did not normalize. The biomarkers remained unchanged at the six-month evaluation and the L-Arginine/ADMA-ratio correlated inversely to pulmonary vascular resistance (PVR) six months post-HT. Conclusions. Plasma L-Arginine concentrations normalize after HT. However, as ADMA is unchanged, the L-Arginine/ADMA-ratio remained low and correlated inversely to PVR. Together these findings suggest that (i) the L-Arginine/ADMA-ratio may be an indicator of pulmonary vascular tone after HT, and that (ii) NO-dependent endothelial function is partly restored after HT. Considering the good postoperative outcome, the biomarker levels may be considered "normal" after HT.